PELATIHAN DAN PENDAMPINGAN IMPLEMENTASI E-LEARNING MARIBELAJAR DAN METODE PEMBELAJARAN BLENDED LEARNING UNTUK PARA GURU SD NEGERI PENJARINGANSARI II/608 SURABAYA - Chrystia Aji Putra; Made Hanindia Prami Swari; Henni Endah Wahanani (Universitas Sanata Dharma, 2022)
Management of learning facilities through good synergy between teachers, students, and parents is certainly needed not only during the pandemic, but also later when schools return to normal face-to-face learning activities as happened before the COVID-19 pandemic hit the world. The key to the formation of a good synergy is through good communication between the three parties, so an easy communication facility is needed. The accumulation of messages on whatsapp and participants can delete messages that have been sent to the management group. Assignment assessment becomes difficult and there is a possibility of missing assignments that have been collected by students in the group. Through this community service activity, the use of information technology is implemented through the development of the MariBelajar E-Learning application that adapts to the needs of students, teachers, and parents, especially at SDN Penjaringansari II/608. Like WhatsApp, the application that was built was made to be easy to use. The application will group students based on the class taken. At the beginning of the display of each class, students and parents will be presented with a menu such as a calendar that contains all activities, both material, task information, discussions, and daily task collection menus, so that all information can be well organized. In addition to system implementation, another agenda is the dissemination of blended learning methods which are a combination of offline and online learning methods that are very suitable to be applied in the current learning period. It is hoped that the socialization provided can be an alternative solution for effective learning methods for each class taught by the teacher at SDN Penjaringansari II/608